Ergot alkaloid biosynthesis in Aspergillus fumigatus: Conversion of chanoclavine-I aldehyde to festuclavine by the festuclavine synthase FgaFS in the presence of the old yellow enzyme FgaOx3 - Wallwey, Christiane; Matuschek, Marco; Xie, Xiu-Lan; Li, Shu-Ming (Organic & biomolecular chemistry, 2010)
Ergot alkaloids are toxins and important pharmaceuticals which are produced biotechnologically on an industrial scale. A putative gene fgaFS has been identified in the biosynthetic gene cluster of fumigaclavine C, an ergot alkaloid of the clavine-type. The deduced gene product FgaFS comprises 290 amino acids with a molecular mass of about 32.1 kDa. The coding region of fgaFS consisting of three exons was amplified by PCR from a cDNA library of Aspergillus fumigatus, cloned into pQE70 and overexpressed in E. coli. The soluble monomeric His(6)-FgaFS was purified by affinity chromatography and used for enzyme assays. It has been shown that FgaFS is responsible for the conversion of chanoclavine-I aldehyde to festuclavine in the presence of the old yellow enzyme FgaOx3. The structure of festuclavine including the stereochemistry was unequivocally elucidated by NMR and MS analyses. Festuclavine formation was only observed when chanoclavine-I aldehyde was incubated with FgaOx3 and FgaFS simultaneously or as a tandem-reaction with a sequence of FgaOx3 before FgaFS. In the absence of FgaFS, two shunt products were formed and did not serve as substrates for FgaFS reaction.